A Metallicity Catalog of Very Metal-poor Main-sequence Turn-off and Red Giant Stars from LAMOST DR10 - Xiangyu Li; Huiling Chen; Yang Huang; Huawei Zhang; Timothy C. Beers; Linxuan Zhu; Jifeng Liu (The Astrophysical Journal Supplement Series)
We present a catalog of 8440 candidate very metal-poor (VMP; [Fe/H] ≤ −2.0) main-sequence turn-off (MSTO) and red giant stars in the Milky Way, identified from low-resolution spectra in LAMOST DR10. More than 7000 of these candidates are brighter than G  ∼ 16, making them excellent targets for high-resolution spectroscopic follow-up with 4–10 m class telescopes. Unlike most previous studies, we employed an empirical calibration to estimate metallicities from the equivalent widths of the calcium triplet lines, taking advantage of the high signal-to-noise ratio in the red arm of LAMOST spectra. We further refined this calibration to improve its reliability for more distant stars. This method enables robust identification of VMP candidates with metallicities as low as [Fe/H] = −4.0 among both MSTO and red giant stars. Comparisons with metal-poor samples from other spectroscopic surveys and high-resolution follow-up observations confirm the accuracy of our estimates, showing a typical median offset of ∼0.1 dex and a standard deviation of ∼0.2 dex.